A porous material of cross-linked adenine-polyethylene glycol diglycidyl ether for copper ion adsorption. (16th June 2021) - Zhang, Longfei; Zhang, Shuai; Wang, Cheng; Li, Wa; Yang, Lirong; Li, Shanggeng; Hu, Jiaming; Zhang, Lin
Abstract: A porous material (PEA) was prepared by the ring opening polymerization of polyethylene glycol diglycidyl ether with adenine in a simple sol-gel method. The structure and composition of PEA were characterized by SEM, FT-IR, BET and XRD. The adsorption experiments of copper ion by PEA at different pH, temperature, contact time and initial concentration were studied. The results show that the PEA is macroporous, the optimum adsorption pH is 5 and the saturated adsorption time is 180 min. The maximum equilibrium adsorption capacity of copper ion is 80.1 mg g −1 at 40 °C according to the Langmuir model and the competitive adsorption test shows that PEA has good adsorption on copper ion, but low effect on cobalt, cadmium and nickel. The repeated adsorption experiments show that PEA could still adsorb 82% of the first adsorption capacity after 5 times elution. These results indicate that the PEA can be used as a practical adsorbent for copper ion adsorption in aqueous solution.